EP596 Value of fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) and sentinel lymph node biopsy (SLN) in endometrial cancer patients: a prospective study. (1st November 2019) - Palaia, I; Di Donato, V; Musella, A; Muzii, L; Perniola, G; Di Pinto, A; Santangelo, G; Boccia, SM; Sassu, CM; Vertechy, L; Musacchio, L; Tomao, F; et al.
Abstract : Introduction/Background: This study aimed to define the role of combination of preoperative PET/CT scan and SLN biopsy for detection of nodal metastasis in Endometrial Cancer (EC) patients. Methodology: All patients affected by EC prospectively collected from January 2014 to August 2016 underwent PET/CT scan and SLN mapping using indocyanine green (ICG) as tracer. Patients with suspicious lymph nodes at FDG-PET/CT underwent selective pelvic lymphadenectomy. In case of undetectable SNL, no further lymphadenectomy was performed if PET/CT scan was negative. Basic descriptive statistics were used to describe outcomes. Results: A total of 83 patients were enrolled in the study. PET/CT scan was suggestive of nodal involvement in 15 patients. SLN were detected bilaterally in 78% of patients. Detection rate was influenced by patient' BMI and learning curve. Five patients were node positive: of these all had hyper metabolic nodes at PET/CT scan, in 1 patient SLN was not detected. Ten out of 15 patients, with suspicious nodal at PET/CT scan, was node negative. After a median follow up of 24 months (range 14–45) all patients are alive. Four patients experienced recurrent disease. No nodal relapse was recorded. Conclusion: Lymphatic mapping with sentinel node biopsy is able to reduce morbidity associated with pelvic lymphadenectomy. Detection rate is strongly improved with learning curve and reduced in morbidly obese patients. PET/CT scan shows high sensitivity for nodal metastasis but moderate specificity and may help to avoid nodal dissection in patients with sentinel node failure. Disclosure: Nothing to disclose.